Enhancing Students’ Vocabulary Mastery through Guessing Word Games: An Engaging Strategy in EFL Classroom - Suleman, Fitri Handayani; Hasan, Hasan (Majesty Journal, 2021)
Vocabulary learning was a very important aspect for students when they are learning English. Students need new learning methods so they can enjoy the ongoing learning process. The teacher should also be able to convey the material well and using media appropriately. The purpose of this study was to determine whether song media can have a significant difference in increasing of students English vocabulary at seventh grade of MTs Darul Falah Islamic Boarding School Enrekang, and to find out whether the use of song media is more effective than the use of conventional media. The population in this study was 60 students. It consists of 2 classes and each class consists of 30 students. From the results of calculations at the time of the pre-test or before treatment, it was obtained the value of t0 = 1.517 < tt = 2.001, which shows that both classes are worthy of study because they do not have a significant difference in increasing of students English vocabulary after being tested using the t-test, but after giving treatment and posttest values ​​obtained t0 = 3.201> tt = 2.001, with a significance level α = 0.05 and df = n1 + n2 - 2 = 58, then t0 is higher than tt which indicates there is a significant difference in increasing of students English vocabulary between classes taught guess word games (experimental class) and classes taught using conventional media (control classes) after being given a pre-test, besides that the use of song media is more effective and has a significant effect than the use of conventional media.